2020
DOI: 10.1111/exd.14144
|View full text |Cite
|
Sign up to set email alerts
|

Can melatonin and its metabolites boost the efficacy of targeted therapy in patients with advanced melanoma?

Abstract: Melanoma is one of the deadliest cancers in the Western world with an increasing incidence. [1,2] Our most recently approved therapies against metastatic melanoma, especially checkpoint inhibitors and targeted therapy with BRAF/MEK inhibitors, have largely replaced chemotherapy. The 5-year survival rate of patients with stage IV melanoma has increased to 15%-20%. [3-5] Nevertheless, the overall survival rate and drug resistance remain a challenge for targeted therapy. According to clinical trials, BRAF kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Furthermore, regulation of their endogenous production/metabolism can serve as a rational strategy for targeted therapies of melanoma patients. Thus, based on results presented here and hypothesized recently Kleszczy ński and Böhm [91] and others [92,93], we are tempted to claim that melatonin, and also its metabolites, may boost commonly used BRAF/MEK inhibitors; however, these investigations still need to be carefully checked using in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, regulation of their endogenous production/metabolism can serve as a rational strategy for targeted therapies of melanoma patients. Thus, based on results presented here and hypothesized recently Kleszczy ński and Böhm [91] and others [92,93], we are tempted to claim that melatonin, and also its metabolites, may boost commonly used BRAF/MEK inhibitors; however, these investigations still need to be carefully checked using in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 76%
“…Notably, a few clinical trials reported increased doses of pharmacotherapy to patients, which was associated with adverse effects such as skin rash, keratoacanthoma, hyperkeratosis, headache, arthralgia, pyrexia, and atopic dermatitis, and 7% to 9% cases were shown to develop cardiac abnormalities that include decreased ejection fraction and interstitial lung diseases such as pneumonitis [ 28 ]. Therefore, due to these ongoing challenges associated with conventional therapies, including adverse side effects, various adjuvant therapies, including melatonin are being explored as repurposed drugs in cellular and preclinical models because of their anticancer properties in melanoma [ 29 ].…”
Section: Therapeutic Options For Melanomamentioning
confidence: 99%
“…Melatonin reduces the rates of cancer initiation, progression, metastasis and migration [ 36 , 37 , 38 , 39 ], angiogenesis, and inflammation [ 40 , 41 , 42 ]. On the other hand, melatonin can regulate the immune system [ 43 , 44 ] and oxidative stress [ 19 , 30 , 38 , 45 , 46 , 47 , 48 ], thereby repressing many malignancies [ 49 ].…”
Section: Melatonin Biosynthesis and Functionmentioning
confidence: 99%